2015
DOI: 10.1111/birt.12206
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Breastfeeding Practices and Success in a Multi‐Ethnic Asian Population

Abstract: The low rates and duration of breastfeeding in this population may be improved with breastfeeding education and support, especially in mothers with lower education. Further work is needed to understand the cultural differences in mode of feeding and its implications for maternal and infant health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
2
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 34 publications
4
45
2
8
Order By: Relevance
“…Similarly, Pang et al conducted a cohort study involving 1030 Singaporean women in early pregnancy and found that the prevalence of breastfeeding at 6 months postpartum varies among the different ethnic groups even after adjusting for maternal education [16]. In our study, we found similar prevalence (79.1% vs 79.9%) of breastfeeding at 5 to 9 weeks postpartum as compared to the National Breastfeeding Survey in 2011 [1].…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, Pang et al conducted a cohort study involving 1030 Singaporean women in early pregnancy and found that the prevalence of breastfeeding at 6 months postpartum varies among the different ethnic groups even after adjusting for maternal education [16]. In our study, we found similar prevalence (79.1% vs 79.9%) of breastfeeding at 5 to 9 weeks postpartum as compared to the National Breastfeeding Survey in 2011 [1].…”
Section: Discussionsupporting
confidence: 77%
“…We have previously reported that breast milk expression is common in the multi-ethnic Asian Singapore population [15]. While the majority of mothers who fed their infants expressed breast milk also fed their infants directly at the breast, we found that a substantial proportion of mothers fed their infants expressed breast milk exclusively at three months postpartum and beyond.…”
Section: Introductionmentioning
confidence: 47%
“…Ethnicity has been pointed out as a significant predictor of how breastfeeding is performed in large continents such as Asia or Africa [16,17]. Thus, within the limitations of the present study, we have found explanatory variables that have been discussed in the EBF practice, but larger studies can increase knowledge in this area.…”
Section: Variablesmentioning
confidence: 68%
“…This loss was greater than that found in the present study; however, the follow-up was performed for a longer period. The difference among studies published in Brazil and worldwide regarding the loss of participants is directly related to the type of study proposed by the authors, the form of interviews (telephone contact or home visit) and the time participants were followed, which indicates that the longer the study period, the greater the sample loss percentage [12,13,15,16].…”
Section: Variablesmentioning
confidence: 99%